Comparing the impact of management on public and private sector nurses in the UK, Italy, and Australia. Issue 4 (3rd April 2018) - Brunetto, Yvonne; Xerri, Matthew; Trinchero, Elisabetta; Beattie, Rona; Shacklock, Kate; Farr-Wharton, Rod; Borgonovi, Elio
ABSTRACT: The research examined the impact of management upon employee outcomes (perceptions of discretionary power, well-being, engagement, and affective commitment), comparing public and private sector nurses in Australia, the United Kingdom, and Italy. Overall, 1, 945 nurses participated in a self-report survey within these core- and laggard-New Public Management countries. While management influenced employee outcomes for each country, there were significant differences between the public and private sectors, with private sector nurses reporting higher perceptions of outcomes. Importantly, nurses' engagement was affected by management practice for each country. This study raises important implications for nurse managers, especially public sector managers, described within.